2006
DOI: 10.12944/cwe.6.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sediment Contamination by Heavy Metals in River Orogodo (Agbor, Delta State, Nigeria)

Abstract: The most often polluted phases of the environmental are the aquatic system, especially the surface water. This is because contaminants in air, soil or on land ultimately end up in the aquatic systems via local precipitation, water surface runoff and leaching of rocks and solid wastes (Forstner and Wiltman, 1983). Sewage, industrial wastes and agricultural chemicals such as fertilizers and pesticides, mineral and petroleum exploration and exploitation are however, the main causes of surface water pollution (Yon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
4
4
1
Order By: Relevance
“…Low levels of Pb recorded in this study (0.9–1.4 mg kg −1 ) are consistent with previous results in Niger Delta (Adeleye, Shelle, and Akinnigbagbe 2011 ; Chindah et al 2009 ). Similarly, low levels of Cd are in agreement with previous findings for the Niger Delta (Otitoju and Otitoju 2013 ; Vincent-Akpu and Mmom 2012 ; Ideriah, David-Omeiema, and Ogbonna 2012 ; Issa et al 2011 ; Adeleye, Shelle, and Akinnigbagbe 2011 ). Concentrations of Cr varied from 4.9 to 5.6 mg kg −1 , which is higher than 0.08–0.31 mg kg −1 reported for sediments from the Abonnema shoreline (Ideriah, David-Omeiema, and Ogbonna 2012 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Low levels of Pb recorded in this study (0.9–1.4 mg kg −1 ) are consistent with previous results in Niger Delta (Adeleye, Shelle, and Akinnigbagbe 2011 ; Chindah et al 2009 ). Similarly, low levels of Cd are in agreement with previous findings for the Niger Delta (Otitoju and Otitoju 2013 ; Vincent-Akpu and Mmom 2012 ; Ideriah, David-Omeiema, and Ogbonna 2012 ; Issa et al 2011 ; Adeleye, Shelle, and Akinnigbagbe 2011 ). Concentrations of Cr varied from 4.9 to 5.6 mg kg −1 , which is higher than 0.08–0.31 mg kg −1 reported for sediments from the Abonnema shoreline (Ideriah, David-Omeiema, and Ogbonna 2012 ).…”
Section: Resultssupporting
confidence: 91%
“…These values were higher than those reported for Ngada River and Cross River (Ayotunde, Offem, and Ada 2012 ; Akan et al 2010 ). The Mn concentrations found here are higher than those (0.5–4.0 mg kg −1 ) in River Orogodo sediment in the Niger Delta (Issa et al 2011 ). The Cu concentrations of 8.8–12 mg kg −1 in Bodo Creek sediments were higher than those observed by Chindah et al ( 2009 ) and Osuji and Onojake ( 2004 ) in the Niger Delta.…”
Section: Resultscontrasting
confidence: 66%
“…While concentrations of copper and nickel in the study area is similar to those found in the sediments of the Benin River, zinc, vanadium and lead concentrations were far above those found in the same river (Akporido and Ipeaiyeda, 2014) and in the Orogodo River in Agbor Delta State (Issa et al, 2011) all in the far northwester flank of the Niger Delta. Metal concentrations from this study were also very much higher than those found in the Bonny River system around Okrika (Marcus et al, 2013) located not more than twenty kilometres northwest of the study area, while manganese concentrations in the Oturuba system were very much above those found in the sediments of the Taylor Creek system in Bayelsa Nigeria (Okafor and Opuene, 2007).These not only shows that the Oturuba Creek is heavily polluted but that heavy metal pollution of river sediments may be more related to local anthropogenic inputs than terrigenous sources.…”
Section: Discussionsupporting
confidence: 71%
“…Sediment also serves as reservoir for pollutants and therefore a potential source of pollutants to the water column, organisms, and ultimately human consumers of those organisms (Issa, 2008). The concentration of Cr was observed 18.907, 15.083, 20.603, 19.957, 20.877 and 20.787 mg/kg in January to June, respectively.…”
Section: Heavy Metal In Sedimentsmentioning
confidence: 99%